2019
DOI: 10.17728/jatp.2714
|View full text |Cite
|
Sign up to set email alerts
|

Development of Mocaf-Wheat Noodle Product with the Addition of Catfish and Egg-White Flours as an Alternative for High-Animal-Protein Noodles

Abstract: This study aimed to determine the best formula and chemical dan sensory properties of noodles made from mocaf-wheat flour supplemented with catfish and egg-white flours. The factorial randomized trial was used in this experiment. The treatment factors consisted of the types of supplementary flour i.e. catfish flour (T1) and egg white flour (T2). These supplementary flour was applied to the mocaf and wheat flour of 70:30 as follows 5, 10, 15, and 20% (w/w) and assigned as P1, P2, P3, and P4. Chemical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
6
0
3
Order By: Relevance
“…The color of the nuggets produced looks dark, this is because the color of the chicken liver tends to darken after steaming. Research by Agustia et al [24] showed that mocafgarut biscuit products with chicken liver substitute darkened because chicken liver contains iron, and products fortified with the iron will have a dull color as a result of complex changes between iron and polyphenols. The use of tapioca flour as a binder and bread flour as a bettering can affect the color during frying due to the Millard reaction.…”
Section: Color Using a Color Readermentioning
confidence: 99%
“…The color of the nuggets produced looks dark, this is because the color of the chicken liver tends to darken after steaming. Research by Agustia et al [24] showed that mocafgarut biscuit products with chicken liver substitute darkened because chicken liver contains iron, and products fortified with the iron will have a dull color as a result of complex changes between iron and polyphenols. The use of tapioca flour as a binder and bread flour as a bettering can affect the color during frying due to the Millard reaction.…”
Section: Color Using a Color Readermentioning
confidence: 99%
“…Food quality can be measured by three properties: chemical, physical, and sensory. Consumer acceptance is primarily determined by quality factors, especially organoleptic (Agustia et al, 2019;Akonor et al, 2017). Organoleptic properties are determined using the human senses: sight, smell, and taste (Chauhan et al, 2018).…”
Section: Organoleptic Testmentioning
confidence: 99%
“…Fresh egg white, as a traditional natural additive, has good gelling and emulsifying properties. Some studies have shown that adding egg white powder in the right amount can boost dough performance, increase the viscoelasticity of noodles, and greatly reduce cooking loss (Agustia et al, 2019; Bai et al, 2022). Thus, the addition of fresh egg white may provide new ideas for obtaining noodles with high mung bean content.…”
Section: Introductionmentioning
confidence: 99%